Promise of India: how Prime Ministers Nehru to Modi shaped the nation (1947-2019) - "Bhagwati, Jaimini" (Gurgaon, 2019)
In this first-of-its-kind book, Jaimini Bhagwati analyses the key political, foreign policy and economic decisions of all the premiers from Jawaharlal Nehru to Narendra Modi, to understand how well they steered the nation on the path of progress and development.
Keywords: Foreign Policy